Drumming in time is easy: social bonding effects of synchrony arise from reduced cognitive load - Bamford, JS; Tarr, B; Miles, L; Cohen, E (Japanese Society for Music Perception and Cognition, 2023)
The synchrony-bonding effect has often been observed, but the mechanisms behind it remain poorly understood. Numerous possible mechanisms have been proposed, however simple perceptual processing explanations have been largely ignored. The present study tested a theory based on processing fluency across two controlled experiments. In the first study, 104 participants completed a drumming task in a within-subjects design in which they also completed a secondary visual attention task. We found that when drumming in non-synchrony, performance was worse on the secondary task, indicating increased cognitive load. In the second study, 82 participants performed a similar drumming task, however instead of the secondary task they were asked to self- report how difficult they found the tapping task and how much they liked the person they were drumming with. Participants reported that drumming in synchrony felt easier and produced greater feelings of social connection than drumming out of synchrony. Taken together, these studies suggest that synchrony may promote processing fluency, which in turn leads to prosocial effects.